2003
DOI: 10.3189/172756403781815663
|View full text |Cite
|
Sign up to set email alerts
|

Tidal bending of glaciers: a linear viscoelastic approach

Abstract: In theoretical treatments of tidal bending of floating glaciers, the glacier is usually modelled as an elastic beam with uniform thickness, resting on an elastic foundation. With a few exceptions, values of the elastic (Young's) modulus E of ice derived from tidal deflection records of floating glaciers are in the range 0.9^3 GPa. It has therefore been suggested that the elastic-beam model with a single value of E º 1GPa adequately describes tidal bending of glaciers. In contrast, laboratory experiments with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
119
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(121 citation statements)
references
References 19 publications
2
119
0
Order By: Relevance
“…The rheological model is the same as that used by Gudmundsson (2011), and a more detailed description can be found there. Work by Reeh et al (2003) showed that linear elastic models of ice were not adequate over tidal timescales, and they proposed instead the use of a linear viscoelastic Burgers model of ice rheology. Following the arguments made in Gudmundsson (2011) we use a nonlinear Maxwell model (consisting of a viscous damper and elastic spring connected in series) which has a close agreement to more complex Burgers model at the relevant timescales.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rheological model is the same as that used by Gudmundsson (2011), and a more detailed description can be found there. Work by Reeh et al (2003) showed that linear elastic models of ice were not adequate over tidal timescales, and they proposed instead the use of a linear viscoelastic Burgers model of ice rheology. Following the arguments made in Gudmundsson (2011) we use a nonlinear Maxwell model (consisting of a viscous damper and elastic spring connected in series) which has a close agreement to more complex Burgers model at the relevant timescales.…”
Section: Methodsmentioning
confidence: 99%
“…Initial measurements of tidal forcing on ice were limited to the surface of the ice shelves (Williams and Robinson, 1980) and the hinging zone where ice flexure occurs near the grounding line (Smith, 1991;Doake et al, 1987). In these regions, tidal effects can be simply described with analytical solutions and elastic beam theory (Holdsworth, 1969(Holdsworth, , 1977Reeh et al, 2003). Measurements made by Anandakrishnan and Alley (1997) on the Kamb ice stream first showed that these effects were not limited to regions within a few ice thicknesses of the ocean boundary but could be transmitted far upstream.…”
Section: Overview Of Previous Studiesmentioning
confidence: 99%
“…Values derived from tidal deflection records of ice shelves are as low as 0.9 GPa, whereas laboratory experiments with ice give E = 9.3 GPa (Vaughan 1995;Reeh et al 2003). We select a value of E = 3.9 GPa for our simulations.…”
Section: (D) Parameter Choicesmentioning
confidence: 99%
“…Reeh et al, 2003;Walker et al, 2012). Boundary conditions for these perturbed momentum equations may be essential (specified velocities) or natural [specified stress rates, using (3), (4) in the weak forms of (11), (12)]; for our rectangular domains, natural boundary conditions amount to zero longitudinal stress (rate) at transverse boundaries and zero shear stress (rate) at lateral boundaries.…”
Section: Modelmentioning
confidence: 99%